Analytical-numerical method for calculating cross-flow tube heat exchangers considering temperature-dependent fluid heat capacities. (February 2022) - Węglarz, Katarzyna; Taler, Dawid; Jaremkiewicz, Magdalena; Taler, Jan; Marcinkowski, Mateusz
Highlights: A new semi-numerical method for the calculation of tube heat exchangers is presented. An exact analytical model for a two-pass cross-current heat exchanger was developed. A numerical model of a two-pass cross-current boiler steam superheater was built. The fluid temperatures obtained by the exact and numerical model were compared. The temperature-dependent specific heat capacities of the fluids were considered. Abstract: The paper presents a mathematical model of a steam reheater in a steam boiler installed in a power unit of 1000 MW. A new numerical-analytical method was used to determine the temperature distribution of steam, flue gas, and the reheater's tube walls. The reheater is a two-pass cross-current heat exchanger. There are 44 panels of tubes on the width of the boiler. The steam flows parallel through 20 pipes in each pass. An analytical model of the superheater was developed with the assumption of the constant physical properties of steam and flue gas. The results of steam and flue gas temperature calculations obtained by the proposed method were compared with the exact method's results. Very high accuracy of estimates was attained even if the whole superheater is divided into a few control volumes. The results of the first and second pass steam temperature calculations were compared using the P-NTU (Effectiveness - Number of Transfer Units) method. A perfect match between the steam temperature and the average temperature of the flue gas at the outlet of the reheater was found. The advantage of the developed method of superheaters modeling is the possibility to model heat exchangers with complex flow systems. The calculations were also carried out for temperature-dependent physical properties of steam and flue gas.